1963
DOI: 10.1037/h0048886
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of nonreinforced responding as a function of the direction of a prior-ordered incentive shift.

Abstract: After a pretraining period in which all Ss were trained to bar press for water, 2 groups of rats were given 4 30-sec. reinforced trials and 4 30-sec. nonreinforced trials daily for 12 days. During each reinforced trial, Ss received continuous reinforcement of a sucrose solution. The concentration of the sucrose was progressively shifted either up or down over the 4 reinforced trials. The group which received the increasing incentives bar pressed reliably less than the decreasing-incentive group during the rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
4
0

Year Published

1963
1963
1970
1970

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…The 5"s given high terminal sucrose concentration were more resistant to extinction than 5"s whose final sucrose concentration was low. The same phenomenon was found by Marx, Tombaugh, Cole, and Dougherty (1963) with a bar-press response.…”
Section: Relative Influence Of Initial and Subsequent R G On Behavior...supporting
confidence: 84%
“…The 5"s given high terminal sucrose concentration were more resistant to extinction than 5"s whose final sucrose concentration was low. The same phenomenon was found by Marx, Tombaugh, Cole, and Dougherty (1963) with a bar-press response.…”
Section: Relative Influence Of Initial and Subsequent R G On Behavior...supporting
confidence: 84%
“…It is concluded that the present results confirm the ones earlier obtained (Marx et al, 1963), thus indicating that the effect on nonreinforcement is not a function of the amount of incentive consumed and extending the generality of the effect to the runway. It should be noted that the present data do not constitute evidence for the effectiveness of the order variable per se ; since this was not separated from the terminal level of the incentive in these experiments.…”
supporting
confidence: 91%
“…The two experiments used essentially the same design as the Marx et al (1963) experiment. Experiment I utilized increasing and decreasing percentages of sucrose concentration, and Exp.…”
mentioning
confidence: 99%
“…Apparatus,-The apparatus was the same as described by Marx et al (1963). In brief, it consisted of eight operant-conditioning boxes in which each bar press (BP) mechanically operated a dipper located below the bar.…”
Section: Experiments I Methodsmentioning
confidence: 99%
“…Others (Campbell, 1958;Guttman, 1953;Young & Green, 1953) indicate that some dimension of the reinforcement properties-taste, receptor sensitivity, or a motivational property, is a more important variable. Marx, Tombaugh, Cole, and Dougherty (1963) trained two groups 1 This research was supported by United States Public Health Service Grant MH00817-10 from the National Institute of Mental Health, United States Public Health Service Grant HD0089S-10 from the National Institute of Child Health and Human Development, and National Science Foundation Grant GB229 from the National Science Foundation. The authors wish to thank Judith E. Peterson for her assistance in collecting the data from Exp.…”
mentioning
confidence: 99%